Компьютерное исследование динамической устойчивости вязкоупругих прямоугольных пластин с переменной жесткостью - Абдикаримов, Р.А.; Протасов, С.Ю. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
By the method of computer simulation the dynamic stability of
viscoelastic isotropic plates with variable thickness on the basis of the Kirchhoff-Love
hypothesis in the geometrically nonlinear formulation for a weakly-singular Koltunov-
Rzhanitsin kernel is investigated. In a wide range of mechanical and geometrical
parameters for fast increasing loads the critical load and critical time are determined.